Imagining the primitive in naturalist and modernist literature - Rossetti, Gina M., 1971- (University of Missouri Press, 2006)
"Examines the depiction of primitive characters in naturalist and modernist texts, focusing on works by Jack London, Frank Norris, Eugene O'Neill, Theodore Dreiser, Willa Cather, Ernest Hemingway, Gertrude Stein, and Nella Larsen"--Provided by publisher